Una prueba exploratoria de la alimentación usando "Tropaeolum tuberrosum" - Bateman, John V. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
As a preliminsy trial in the use of Tropaeolum tuberosum as feed, six weanling pigs were divided into three groups receiving cooked tubers plus grain and skim milk. saw tubers plus grain and skim milk, and grain and skim milk, respectively